A phase II trial of trastuzumab plus weekly ixabepilone and carboplatin in patients with HER2-positive metastatic breast cancer: an Eastern Cooperative Oncology Group Trial - Moulder, Stacy (2010)
The epothilone B analogue, ixabepilone, binds to β-tubulin, is effective for taxane-refractory metastatic breast cancer (MBC), and may be given every 3 weeks or weekly. We evaluated the efficacy of weekly ixabepilone (I) plus trastuzumab (T) and carboplatin (C) as first line therapy in HER2 + MBC. Patients with HER2+ (3+ by IHC or FISH amplified) MBC received I (15 mg/m(2) IV) and C (area under the curve, AUC = 2 IV) on days 1, 8, and 15 of a 28-day cycle for a maximum of 6 cycles, plus weekly T (4 mg/kg loading dose then 2 mg/kg IV) during chemotherapy then every 3 weeks (6 mg/kg IV) until disease progression. The primary objective was to determine whether the combination was associated with a response rate (RR) of at least 75%. Fifty-nine patients were treated, and 39 had HER2 overexpression confirmed in a central lab (cHER2+). For all treated patients, objective response occurred in 26 patients (44%; 95% CI 31–58%), median time to progression was 8.2 months (95% CI 6.3–9.9), and median overall survival was 34.7 months (95% CI 25.7 to [not reached]). Results were comparable for cHer2+ cancers. Grade 3–4 adverse events included neutropenia (49%), thrombocytopenia (14%), fatigue (12%), nausea (7%), diarrhea (7%), and neuropathy (7%). One patient died from treatment complications during cycle 1. Weekly ixabepilone and carboplatin plus trastuzumab have an acceptable toxicity profile, but are not likely to be associated with an RR of 75% in HER2+ MBC. Efficacy appears comparable to paclitaxel, carboplatin, and trastuzumab.